2013
DOI: 10.1016/j.neubiorev.2013.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Striatal ups and downs: Their roles in vulnerability to addictions in humans

Abstract: Susceptibility to addictive behaviors has been related to both increases and decreases in striatal function. Both profiles have been reported in humans as well as in animal models. Yet, the mechanisms underlying these opposing effects and the manner in which they relate to the behavioral development and expression of addiction remain unclear. In the present review of human studies, we describe a number of factors that could influence whether striatal hyper- or hypo-function is observed and propose a model that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
117
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(119 citation statements)
references
References 269 publications
(289 reference statements)
2
117
0
Order By: Relevance
“…Pattern, total dose, and abstinence periods need to be taken into account when modeling the behavioral and neurochemical processes involved in addiction. Cocaine sensitization has been difficult to demonstrate in humans, suggesting that either sensitization does not occur in humans or that it occurs during a part of the addiction process that has not been studied extensively (Leyton and Vezina, 2013). It is possible that early in the drug abuse process administration of cocaine is intermittent, leading to a sensitized cocaine response that facilitates continued drug use, while after long-term use there is tolerance to acute drug effects, an effect that has been reported in human subjects (Mendelson et al, 1998;Reed et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Pattern, total dose, and abstinence periods need to be taken into account when modeling the behavioral and neurochemical processes involved in addiction. Cocaine sensitization has been difficult to demonstrate in humans, suggesting that either sensitization does not occur in humans or that it occurs during a part of the addiction process that has not been studied extensively (Leyton and Vezina, 2013). It is possible that early in the drug abuse process administration of cocaine is intermittent, leading to a sensitized cocaine response that facilitates continued drug use, while after long-term use there is tolerance to acute drug effects, an effect that has been reported in human subjects (Mendelson et al, 1998;Reed et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely viewed as arising from the representativeness heuristic, the belief that a short segment of a random sequence should reflect the overall distribution (Rabin, 2002;Ayton and Fischer, 2004). Another archetypal distortion is the "illusion of control," referring to the interpretation of skill involvement in situations that are governed by chance alone (Langer, 1975;Stefan and David, 2013). Illusory control can be fostered by a various psychological features of games, such as the involvement of a choice (e.g., choosing a lottery ticket), instrumental action (e.g., throwing a roulette ball), or apparent competition (Langer, 1975).…”
Section: Gambling-related Cognitive Distortionsmentioning
confidence: 99%
“…Another archetypal distortion is the "illusion of control," referring to the interpretation of skill involvement in situations that are governed by chance alone (Langer, 1975;Stefan and David, 2013). Illusory control can be fostered by a various psychological features of games, such as the involvement of a choice (e.g., choosing a lottery ticket), instrumental action (e.g., throwing a roulette ball), or apparent competition (Langer, 1975). A recent study using a contingency judgment task from the associative learning literature found that pathological gamblers displayed a greater tendency to overestimate their control of positive outcomes than nongambling participants (Orgaz et al, 2013).…”
Section: Gambling-related Cognitive Distortionsmentioning
confidence: 99%
“…26 The basis and meaning of these low DA responses, however, remain unclear. They could reflect neurotoxic effects in late-stage addictions, 27 heritable endophenotypes, conditioned inhibitory effects induced by cues that signal the absence of reward, 5,28 or some combination of these effects (e.g., initial predispositions aggravated by rapidly developing conditioned effects and laterstage neurotoxicity).…”
mentioning
confidence: 99%
“…5,28 In comparison, augmented striatal responses have been seen when high-risk individuals are tested in the presence of drug-paired cues. 5,13,28 Indeed, across stages of addiction, striatal DA release is induced by drug-paired cues alone.…”
mentioning
confidence: 99%